Chlamydia Screening in Juvenile Corrections: Even Females Considered to Be at Low Risk Are at High Risk. (January 2016) - Torrone, Elizabeth; Beeston, Tara; Ochoa, Rosemari; Richardson, Marjorie; Gray, Tom; Peterman, Thomas; Katz, Kenneth A.
The Centers for Disease Control and Prevention recommends chlamydia screening at intake for all females in juvenile detention facilities. Identifying factors predictive of chlamydia could enable targeted screening, reducing costs while still identifying most infections. This study used demographic, arrest, and health data to identify factors associated with chlamydia among females aged 12 to 18 years entering a juvenile detention facility in San Diego during January 2009 to June 2010. The study created different screening criteria based on combinations of factors associated with infection and calculated sensitivity and proportion screened for each criterion. Overall chlamydia prevalence was 10.3% and was 4.2% among females reporting no sexual risk factors. No acceptable targeted screening approach was identified. High prevalence, even among females without risk factors, supports universal screening at intake.